A randomized controlled trial to evaluate the impact of pharmacist-led clinical interventions on the health-related quality of life among TB patients - Khan, Farman Ullah; Khan, Faiz Ullah; Aqeel, Muhammad Tahir; Hayat, Khezar; Chang, Jie; Rehman, Asim ur; Fang, Yu (Frontiers in Pharmacology, 2023)
Abstract Background: The study was designed to evaluate the impact of pharmacist-led clinical interventions on the health-related quality of life among tuberculosis patients in Pakistan. Methods: A randomized, controlled prospective study was carried out in a Pakistan Institute of Medical Sciences hospital tuberculosis (TB) control center. Participants who visited the TB center between September 2020 and December 2021 were randomly assigned to two clusters’ usual care (UC group) vs. intervention group (pharmaceutical care group) in a 1:1 ratio by simple envelope technique. In intervention group a patient receives centred care that encompasses informed decision making can increase quality of care and monitoring of adverse drug events. While the control group received routine TB treatment at the hospital. The EuroQol-5D-3L instrument was used to assess health-related quality of life (HRQoL) at baseline and at the third and sixth months of the treatment time period. Results: A total of 503 patients were eligible, out of the total 426 were included in the study. At the end of the study, n=205 of the patients in the interventipn group and n=185 in the control group were analyzed. In the intervention group, the EQ-5D-3L health utility score improved significantly (p<0.001), (from baseline mean ± SD 0.40 ± 0.36 to six month of the treatment 0.89 ± 0.09, while in the control group from 0.42 ± 0.35 to 0.78 ± 0.27. In multivariate regression analysis, the varaibles which remained statistically associated (p<0.001), with HRQoL (unstandardized β [95% confidence interval] of control group were: gender female vs. male (-0.039 [-0.076 to -0.003], body weight less than 40 kg vs. more than 40 kg (-0.109 [-0.195 to -0.024] , patients with any comorbidity vs. without comorbidity (-0.136 [-0.252 to -0.020] , Smoker vs. non-smokers (-0.204 [-0.291 to -0.118]. The study did not find any statistically significant associations between the intervention groups' variables and HRQoL. Conclusion: Patient-centered care interventions led by pharmacists as part of care coordination increased HRQoL for TB patients significantly. According to this study, clinical pharmacists should be included in the interdisciplinary clinical staff for TB patient management.